Mobile Apps as Audience-Centered Health Communication Platforms - Michael Mackert; Dorothy Mandell; Erin Donovan; Lorraine Walker; Mike Henson-García; Lindsay Bouchacourt (JMIR Publications, 2021)
Health communication campaigns often suffer from the shortcomings of a limited budget and limited reach, resulting in a limited impact. This paper suggests a shift of these campaigns to audience-centered communication platforms-particularly, apps on mobile phones. By using a common platform, multiple interventions and campaigns can combine resources and increase user engagement, resulting in a larger impact on health behavior. Given the widespread use of mobile phones, mobile apps can be an effective and efficient tool to provide health interventions. One such platform is Father's Playbook, a mobile app designed to encourage men to be more involved during their partner's pregnancy. Health campaigns and interventions looking to reach expectant fathers can use Father's Playbook as a vehicle for their messages.